ANALYZING THE PROCESSES OF ANALYTICAL PROCESSING OF INVENTORY ACCOUNTING INFORMATION FOR THE PURPOSE OF ACCOUNTABILITY (International Journal of Innovative Technologies in Economy, 2024)
Topicality. The importance of financial and management reporting in enterprises plays a greater role in the effective presentation and control of resources. These reports allow for more efficient organization and rapid adjustment of business management processes, taking into account the importance of backup data.Aim and tasks. This research will examine in detail the theoretical importance and analytical use of reserve data in financial and management reporting. This article provides information on inventory accounting and how it is important for an enterprise, threats that may arise as a result of improper accounting, and the theoretical importance of analytical accounting.Materials and methods. Data Collection, literature review, policy implications were used in the study. Analytical accounting offers analysis and evaluation of inventories by material types and prices. This includes analysis of material movements, evaluation of material types, diversification, identification of safety points and management of material operations. Analytical analysis results contribute to the determination and development of material management policy.Research results. The greatest advantage of the article is that it combines the theoretical and practical aspects of analysis and emphasizes the value of analysis, reflecting important steps and practical tips for material resource management and production process analysis. This helps to develop the material handling process in an effective and safe manner.Conclusion. The accounting of the quantity of materials is carried out by the persons responsible for the material in the warehouse accounting book according to the first documents. The balance of materials as of the 1st of each month is transferred from the warehouse accounting book to the balance table by the accounting staff or the warehouse manager. Then the balance sheet is reconciled with the data of the synthetic account. Thus, in the application of the balance method, accounting does not repeat the work that would be done by materially responsible persons for accounting of materials, and instead organizes control over their work.